Tourism experience and quality of life among elderly tourists - Kim, H.; Woo, E.; Uysal, Muzaffer (Pergamon, 2015)
The main purpose of this research is to investigate the relationship between the travel behavior of elderly tourists and overall quality of life. Specifically, the study examines the interrelationships between six main constructs: involvement, perceived value, satisfaction with trip experience, leisure life satisfaction, overall quality of life, and revisit intention. Using a sample drawn from elderly tourists in South Korea, the research model investigates nine hypotheses using a structural equation modeling approach. The results show that all nine of the hypotheses are supported.